Grammatical changes in the translation process in the interpretation of John Green's The Fault in Our Stars (Eurasian Scientific Herald, 2023)
In this article, one of the changes that occur in the translation process, grammatical change, is discussed in detail during the analysis of John Green's The Fault in Our Stars. Below are some examples of grammatical change to better understand this type of change.